1998
DOI: 10.1104/pp.118.3.751
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Photomixotrophic Tobacco Cells Resistant to Protoporphyrinogen Oxidase-Inhibiting Herbicides

Abstract: Peroxidizing herbicides inhibit protoporphyrinogen oxidase (Pro-tox

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
29
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 40 publications
2
29
0
Order By: Relevance
“…Tobacco Mitochondrial Protox Homolog-To isolate cDNA encoding the spinach homolog of tobacco mitochondrial Protox, one set of specific oligonucleotide primers (SMT-1F and SMT-1R) was synthesized based on the PPX-II sequence from N. tabacum (tobacco) (13,21). PCR amplification of cDNA from spinach produced a 565-bp product.…”
Section: Isolation and Characterization Of Spinach Cdna Encoding Amentioning
confidence: 99%
See 2 more Smart Citations
“…Tobacco Mitochondrial Protox Homolog-To isolate cDNA encoding the spinach homolog of tobacco mitochondrial Protox, one set of specific oligonucleotide primers (SMT-1F and SMT-1R) was synthesized based on the PPX-II sequence from N. tabacum (tobacco) (13,21). PCR amplification of cDNA from spinach produced a 565-bp product.…”
Section: Isolation and Characterization Of Spinach Cdna Encoding Amentioning
confidence: 99%
“…Several lines of data provide strong evidence that the herbicide resistance of YZI-1S cells is due to the overproduction of mitochondrial Protox, even though the primary target of the herbicide is chloroplast Protox. In the resistant cells, excess Protogen generated by inhibition of chloroplast Protox is rapidly utilized for heme synthesis in mitochondria by the abnormally high level of mitochondrial Protox, thus preventing the accumulation of Proto IX (21). This suggests that mitochondrial Protox is also important in preventing the accumulation of the photosensitizer, Proto IX, and in maintaining the flow of tetrapyrrole precursors for heme and chlorophyll biosynthesis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…19) An analysis of the Protox cDNA sequences in YZI-1S and wild-type cells shown that there was no mutation in either the plastidal or mitochondrial Protox-encoding gene in YZI-1S cells. 20) A northern blot analysis has revealed that the expression level of plastid Protox mRNA was almost the same in both wild-type and YZI-1S cells, whereas mitochondrial Protox mRNA was expressed by up to 10 times more in YZI-1S cells. These data led us to speculate that the S23142 resistance of YZI-1S cells was due to the overproduction of mitochondrial Protox, even though the primary target of S23142 was plastidal Protox.…”
mentioning
confidence: 95%
“…These data led us to speculate that the S23142 resistance of YZI-1S cells was due to the overproduction of mitochondrial Protox, even though the primary target of S23142 was plastidal Protox. 20) However, it remained unknown whether the mitochondrial Protox protein levels and W or activity were actually increased in YZI-1S cells, and whether this was truly responsible for S23142 resistance. Furthermore, the mechanism by which mitochondrial Protox was overexpressed also remained unresolved.…”
mentioning
confidence: 99%